Analysis of the spatiotemporal mechanism of high temperature on residents’ irritability in Beijing based on multiscale geographically weighted regression model - Huang, Huanchun; Liu, Xuan; Ren, Lijian (Frontiers in Ecology and Evolution, 2022)
The emotional health of urban residents is increasingly threatened by high temperatures due to global heating. However, how high temperature affects residents' emotional health remains unknown. Therefore, this study investigated the spatiotemporal pattern of temperature's impact on residents' irritability using data from summer high-temperature measurement and emotional health survey in Beijing, combined with remote sensing images and statistical yearbooks. In detail, this study formulated a multiscale geographically weighted regression (MGWR) model, to study the differentiated and spatial influence of high-temperature factors on emotion. Results show: From 09:00 to 20:00, irritability level rose first then gradually dropped, with a pattern of "aggregated-highly fragmentated-aggregated". Irritability is very sensitive to intercept and building density (BD), Other variables all have spatial heterogeneity (except for vegetation coverage (VC) or road network density (RND) as they are global variables), including normalized difference vegetation index (NDVI), water surface rate (WSR), floor area ratio (FAR), and Modified Normalized Difference Water Index (MNDWI) (sorted from the smallest to the largest in scale). Irritability is negatively correlated with NDVI, WSR, and RND, while positively correlated with intercept, MNDWI, VC, FAR, and BD. Influence on irritability: WSR < NDVI < BD < MNDWI < RND < intercept < VC < FAR.